A review on recent advances in the applications of surface-enhanced Raman scattering in analytical chemistry - Fan, Meikun; Andrade, Gustavo F.S.; Brolo, Alexandre G. (Analytica chimica acta, 2020)
This review is focused on recent developments of surface-enhanced Raman scattering (SERS) applications in Analytical Chemistry. The work covers advances in the fabrication methods of SERS substrates, including nanoparticles immobilization techniques and advanced nanopatterning with metallic features. Recent insights in quantitative and sampling methods for SERS implementation and the development of new SERS-based approaches for both qualitative and quantitative analysis are discussed. The advent of methods for pre-concentration and new approaches for single-molecule SERS quantification, such as the digital SERS procedure, has provided additional improvements in the analytical figures-of-merit for analysis and assays based on SERS. The use of metal nanostructures as SERS detection elements integrated in devices, such as microfluidic systems and optical fibers, provided new tools for SERS applications that expand beyond the laboratory environment, bringing new opportunities for real-time field tests and process monitoring based on SERS. Finally, selected examples of SERS applications in analytical and bioanalytical chemistry are discussed. The breadth of this work reflects the vast diversity of subjects and approaches that are inherent to the SERS field. The state of the field indicates the potential for a variety of new SERS-based methods and technologies that can be routinely applied in analytical laboratories. [Display omitted] •This review covers recent advances of SERS applications in analytical chemistry.•Progresses in substrate development are discussed.•New types of devices that use SERS as a detection platform have been introduced.•SERS for bioanalytical applications is the area with most activity in the field.•New SERS quantification techniques are now available.